A narrative review on techniques of iris replication in an ocular prosthesis - Sharayu Vinod Nimonkar; Vikram Murlidhar Belkhode; Chinmayee Dahihandekar; Pranali Vinod Nimonkar; Sweta Pisulkar (Wolters Kluwer Medknow Publications, 2023)
The disfigurement associated due to the loss of an eye can cause a significant physical and psychological disturbance. Psychological distress among such unfortunate patients can be reduced by providing an artificial eye. Rehabilitating such patients with an ocular defects is the most challenging task for a prosthodontist. The custom-made ocular prostheses are preferred over the prefabricated stock eye shells as it provides intimate contact with the tissue bed, enabling an ideal fit. For an esthetic ocular prosthesis, the precise positioning of an iris is a primary requirement to avoid the squint eye appearance. Various case reports are documented in the literature for centralizing the iris in the prosthetic eye. This review article explores the established methods and techniques for positioning the iris in a custom-made ocular prosthesis.